A ternary hybrid model for analysis of enhanced heat transport in non-Newtonian nanofluid over cylindrical geometry with effect of infinite shear rate viscosity - Hakim AL Garalleh (Results in Engineering)
Ternary hybrid nanofluids in vertical configurations optimize the thermal management systems, improved energy efficiency and performance in heat exchangers, solar collectors, and cooling systems. This article brings attention to investigate the enhanced thermal performance in ternary hybrid nanofluid over a vertical cylinder. The investigation is particularly focused on impact of thermal radiation, infinite shear rate and viscous dissipation in a convective transport of ternary hybrid nanofluid over the vertical cylinder under the influence of MHD consequences. Based on assumptions of current study, the governing partial differential equations (PDEs) are formed and then transformed into ODEs for numerical solution. The resulting system of first order equation are numerically solved by bvp4c MATLAB tool. Furthermore, Levenberg-Marquardt neural network (LMNN) artificial neural network procedure (ANN) scheme is utilized. Fluid profile such as velocity and temperature are depicted with effectiveness of some influential physical parameters. The results are interpreted by MATLAB and statistical illustrations. The best validation performance occurred at 0.00000000866, 0.0000005397, and 0.0000007780 at 1000, 571, 1000 epochs, while values i.e., 0.000508, 0.000338, 0.000127 demonstrates the best error in histogram. Regression values are reasonable in different scenarios for all subcases, which reflects the best approximations and demonstrates the linear link between input and output data. The velocity profile of fluid declined with augmentation in numeric values of Weissenberg number. The increasing values of shear rate viscosity parameter intensifies the magnitude of velocity of ternary hybrid nanofluids. Rapid Heat transfer is noted for ternary fluid compared to di-hybrid nanofluids with augmented values of thermal radiation parameter. Mobility of ternary hybrid nanofluids has increased over time for greater values of curvature parameter, which escalates the temperature profile. Slightly improvement in seen in physical quantities for different categories of nanofluids. Moreover, enhanced heat transport rate is seen in ternary nanofluid, as compared to bi-hybrid and nanofluid due to synergistic effect caused by ternary nanoparticles with varying concentration of volume frictions.